2016
DOI: 10.1007/s10877-016-9919-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an arterial line improves response to simulated hypotension and pulseless electrical activity

Abstract: With pulseless electrical activity (PEA) emerging as one of the leading cardiac arrest arrhythmias, the rapid response and accurate diagnosis of PEA is essential to improve survival rates. Although the use of invasive blood pressure monitoring to more quickly detect changes in blood pressure is widespread, evidence for its use is largely anecdotal and placement is not without risk. This is a prospective, multi-center, randomized controlled trial involving 58 senior anesthesiology residents undergoing a simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In light of the role as an early predictor of ROSC, the dynamic changes in paO 2 between 0 and 10 min could provide additional information with the level of ETCO 2 . Therefore, this could be another piece of evidence to support the current guidelines on performing arterial catheterization during CPR 28 30 .…”
Section: Discussionmentioning
confidence: 85%
“…In light of the role as an early predictor of ROSC, the dynamic changes in paO 2 between 0 and 10 min could provide additional information with the level of ETCO 2 . Therefore, this could be another piece of evidence to support the current guidelines on performing arterial catheterization during CPR 28 30 .…”
Section: Discussionmentioning
confidence: 85%
“…Direct, continuous ABP monitoring allows faster recognition of CPA and initiation of CPR, and so is preferred over intermittent noninvasive monitoring if feasible. 178 A single veterinary study was evaluated in which the relationship between Doppler blood pressure (DopBP) and survival or response to treatment in critically ill cats was investigated. 180 This was a retrospective study of 83 cats, and there was a significantly higher frequency of mortality in hypotensive cats.…”
Section: Justification Of Treatment Recommendationsmentioning
confidence: 99%
“…For the outcome of time to start CPR , 1 clinical trial of simulated anesthetic events in people (very low quality of evidence, downgraded for very serious indirectness and serious imprecision) addressed the PICO question 178 . As described above, the group with access to invasive blood pressure monitoring information initiated chest compressions 17 seconds sooner than the group with only indirect blood pressure monitoring.…”
Section: Monitoring Patients At Risk Of Cpamentioning
confidence: 99%
See 1 more Smart Citation
“…7 A simulation study found that residents who were provided with invasive blood pressure monitoring were quicker to palpate pulses, initiate chest compressions, and administer adrenaline than residents who were provided with only noninvasive blood pressure monitoring. 17 A different study demonstrated that the presence of continuous arterial blood pressure monitoring resulted in improved quality of compressions during simulated cardiac arrest. 18 Transoesophageal echocardiography has been used to identify the cause of intraoperative cardiac arrest and guide management in several observational case series.…”
Section: Identification Of Cardiac Arrestmentioning
confidence: 99%